2021
DOI: 10.17843/rpmesp.2021.382.6764
|View full text |Cite
|
Sign up to set email alerts
|

Situación de la comorbilidad tuberculosis y diabetes en personas adultas en el Perú, 2016-2018

Abstract: Objetivo: Describir las características de los pacientes adultos con tuberculosis (TB) y diabetes mellitus (DM) en el Perú, y explorar la asociación de la DM y la mortalidad en personas con TB. Materiales y métodos: Se realizó un análisis secundario de la base de datos del Sistema de Información Gerencial de Tuberculosis de la Dirección de Prevención y Control de Tuberculosis del Ministerio de Salud de Perú. Se incluyeron aquellos pacientes adultos que iniciaron tratamiento con el esquema de TB sensible a los … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Our findings revealed a distinct dietary pattern in the TB–dysglycemia group, which was associated with an increased risk of unfavorable anti-TB treatment outcomes. The initial analyses of our study demonstrated a high frequency of dysglycemia in the Peruvian population with TB, which is consistent with previous reports on DM prevalence in Peru ( 16 ) and in similar cohorts from low-and middle-income countries, such as South Africa, India, and Brazil ( 30 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings revealed a distinct dietary pattern in the TB–dysglycemia group, which was associated with an increased risk of unfavorable anti-TB treatment outcomes. The initial analyses of our study demonstrated a high frequency of dysglycemia in the Peruvian population with TB, which is consistent with previous reports on DM prevalence in Peru ( 16 ) and in similar cohorts from low-and middle-income countries, such as South Africa, India, and Brazil ( 30 ).…”
Section: Discussionsupporting
confidence: 92%
“…Both dysglycemia and malnutrition can increase the incidence of TB ( 13 , 14 ) and the risk of unsuccessful anti-TB treatment outcomes, such as failure, recurrence, and death ( 6 , 14 , 15 ). Peru, one of the South American countries most affected by TB, had approximately 28,892 new cases in 2019, of which 9.7% presented DM ( 16 ). Peruvian people with TB-DM comorbidity had a higher mortality rate (7.2%) between 2016 and 2018 than normoglycemic people (5.4%) in the same period ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Entre el 2016 y 2018, los adultos peruanos que tenían tuberculosis susceptible mostraron una mayor incidencia de DM en comparación con el VIH e incluso en comparación con adicciones como el alcoholismo, el tabaquismo y la drogadicción, lo que la convirtió en la enfermedad mórbida más común entre las registradas en el sistema de información para el manejo de la tuberculosis. 5 Según la Organización Mundial de la Salud (OMS), México tiene un alto índice en la diabetes, lo cual es la principal causa de muerte, teniendo 14 millones de personas con diabetes en este país, esto va a generar que sea un tema amplio de investigación y se obtenga conocimiento de esta enfermedad. Por lo tanto, si es un problema de salud, se deben plantear políticas para fomentar el consumo de alimentos saludables para su propio bienestar.…”
Section: Introductionunclassified
“…1 In low-and middle-income countries (LMIC), TB is one of the main causes of significant mortality, 2 especially in patients with comorbidities. The most common and well-described comorbidities in TB cases are HIV infection, which correlation with TB is well established; 3 diabetes mellitus (DM), which threatens the continuing efforts to control TB; 4 alcohol abuse; 5 smoking; 6 depression, which has a negative impact in clinical manifestations and treatment adherence; 7 and more recently reported as an emerging TB comorbidity, COPD. 8 A strong relationship between TB, DM and depression has been established in multiple studies.…”
Section: Introductionmentioning
confidence: 99%